Cyclic olefin polymer resin foam sheet

By forming fine bubbles of less than 20 μm in the cyclic olefin resin sheet, a cyclic olefin-based polymer resin foamed sheet with excellent dielectric properties, light reflection properties and surface quality was prepared, and the prior art was solved The problem is that cyclic olefin-based resin foam is difficult to maintain low dielectric characteristics in high-frequency applications.

CN119452022APending Publication Date: 2025-02-14FURUKAWA ELECTRIC CO LTD

Patent Information

Application Number
CN202480003218.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-03-15
Filing Date
2024-01-22
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing cyclic olefin resin foams are difficult to maintain low dielectric properties in high-frequency applications and lack excellent light reflection characteristics and surface quality.

Method used

By forming fine bubbles with an average bubble diameter of less than 20 μm in the resin sheet, combined with the characteristics of the cyclic olefin homopolymer or copolymer, a cyclic olefin-based polymer with excellent dielectric properties, light reflection properties and surface quality was prepared by combining the characteristics of the cyclic olefin homopolymer or copolymer. Resin foamed sheet.

Benefits of technology

It realizes the maintenance of low relative dielectric constant and low dielectric loss factor in high-frequency applications, and has excellent light reflection characteristics and surface quality, and is suitable for applications such as high-frequency electrical parts and light reflector plates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005212541650000031
    Figure BDA0005212541650000031
  • Figure BDA0005212541650000032
    Figure BDA0005212541650000032
  • Figure BDA0005212541650000051
    Figure BDA0005212541650000051
Patent Text Reader

Abstract

The purpose of the present invention is to provide a cyclic olefin polymer resin foam sheet which maintains the stability of mechanical properties or thermal properties and achieves excellent light reflection properties and dielectric properties (low relative permittivity and low dielectric loss factor) and surface quality. The present invention obtains a cyclic olefin polymer resin foam sheet which comprises either a monomer of a cyclic olefin homopolymer (A) or a monomer of a cyclic olefin copolymer (B), or a mixture of the cyclic olefin homopolymer (A) and the cyclic olefin copolymer (B), and which has an average bubble diameter of 1-20 [mu] m. As a result, it is possible to obtain a cyclic olefin polymer resin foam sheet having excellent light reflection properties, dielectric properties (low relative dielectric constant, low dielectric loss factor) and surface quality.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a cyclic olefin polymer resin foamed sheet. Background Art

[0002] Cyclic olefin resins are superior to conventional non-cyclic olefin resins in physical properties such as thermal stability, chemical stability, and elastic modulus, and are widely used in optical fields such as optical films, packaging materials, medical / inspection equipment, and electronic devices. In the field of foams, various resin foams using cyclic olefins as base resins have also been proposed.

[0003] Patent Document 1 discloses a cyclic polyolefin resin having a porosity of 95% or more obtained by gas foaming. This can provide a resin foam having excellent thermal insulation and environmental performance and excellent resistance to moisture and heat. Regarding the cell diameter, it is disclosed that the peak value of the cell diameter distribution is 36 μm to 80 μm.

[0004] Patent Document 2 discloses a cycloolefin copolymer derived from a norbornene-based compound that can be obtained by crosslinking and foaming. Therefore, it is considered to be particularly suitable for such use because it has high resistance to warm water and hot water and does not absorb water due to its chemical structure. Regarding the average cell diameter, an average cell diameter of about 40 μm to about 200 μm is disclosed.

[0005] Patent Document 3 discloses an ethylene-cyclic olefin random copolymer obtained by copolymerizing ethylene and a norbornene-based compound, which can be obtained by injection foaming using carbon dioxide. Thus, it is believed that a foam of a cyclic olefin-based resin having excellent heat resistance and damping properties in a wide temperature range can be provided while being excellent in rigidity, heat resistance, heat aging resistance, chemical resistance, solvent resistance, dielectric properties, etc. There is no record of the bubble diameter of the foam.

[0006] Patent document 4 discloses a coaxial cable with a foaming degree of 80% to 90% obtained by using nitrogen extrusion foaming, in which a resin composition containing a cyclic olefin resin, a low-density polyethylene and / or a linear low-density polyethylene is used as an insulating layer material. Thus, it is believed that a coaxial cable having a lateral pressure resistance sufficient to be used as a coaxial cable and an insulating layer with a higher foaming degree of the insulator layer can be obtained. In addition, since the foaming degree of the insulating layer in the coaxial cable is high, the dielectric loss factor and relative dielectric constant of the insulating layer become low, and it is believed that it can be well used as a high-frequency coaxial cable.

[0007] Patent document 5 discloses a method for producing cyclic olefin resin foamed particles, which produces foamed particles for molding in a mold by foaming foamable particles containing a cyclic olefin resin as a base resin and an inorganic physical foaming agent. It is believed that a foamed molded body with good appearance can be obtained. There is no record about the bubble diameter. [Prior art literature] [Patent Document]

[0008] Patent Document 1: Japanese Patent Application Publication No. 2013-189484 Patent Document 2: Japanese Patent Publication No. 11-514680 Patent Document 3: Japanese Patent Laid-Open No. 11-100454 Patent Document 4: International Publication No. WO2009 / 041116 Patent Document 5: Japanese Patent Application Publication No. 2017-179238 Summary of the invention [Problems to be solved by the invention]

[0009] On the one hand, cyclic olefin resins are expected to be used in high-frequency-related components, especially because they have a low relative dielectric constant and a low dielectric loss factor that are specific to their molecular structure. In particular, foamed cyclic olefin resins are expected to be used in megahertz band components that are expected to expand in the future. However, if the same low dielectric properties are to be exhibited at megahertz frequencies, microfoamed fine bubbles are considered to be necessary. Therefore, an object of the present invention is to provide a cyclic olefin polymer resin foamed sheet which maintains stability of mechanical properties or thermal properties and achieves excellent light reflection characteristics and dielectric properties (low relative dielectric constant, low dielectric loss factor) and surface quality. [Solution to the problem]

[0010] The present inventors have conducted intensive studies in view of the above problems and have found that the above required properties can be satisfied by forming fine bubbles having a specific average bubble diameter or less in a resin sheet. The present invention has been completed based on the above findings. That is, the present invention is a cyclic olefin polymer resin foamed sheet, which is composed of any one of a monomer of a cyclic olefin homopolymer (A) or a cyclic olefin copolymer (B), or a mixture of a cyclic olefin homopolymer (A) and a cyclic olefin copolymer (B), and has an average cell diameter of 20 μm or less.

[0011] The cyclic olefin polymer resin foamed sheet may be one in which the cyclic olefin copolymer (B) is a cyclic olefin elastomer, and the cyclic olefin elastomer is added in an amount of 1 to 20 parts by mass based on 100 parts by mass of the cyclic olefin homopolymer (A).

[0012] It can also be a cyclic olefin polymer resin foam sheet, in which the cyclic olefin homopolymer (A) or the cyclic olefin copolymer (B) has a repeating unit represented by any one of the following formulas (a3), (b3), (c2), (d1), (e3), and (f3). [Chemical formula 1] In the formula, R 1 and R 2 are each independently a hydrogen atom, an alkyl group having 1 to 10 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an alkynyl group having 2 to 10 carbon atoms, an aryl group having 6 to 18 carbon atoms, a hydroxyl group, a halogen atom, or a carboxyl group, and R 1 and R 2 They can also be bonded to each other to form a ring. 3 It is a hydrogen atom, an alkyl group having 1 to 10 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an alkynyl group having 2 to 10 carbon atoms, an aryl group having 6 to 18 carbon atoms, a hydroxyl group, a halogen atom, a carboxyl group, an acyl group having 2 to 12 carbon atoms, or an alkoxycarbonyl group having 2 to 12 carbon atoms.

[0013] The cyclic olefin resin foamed sheet may be one in which the cyclic olefin homopolymer (A) or the cyclic olefin copolymer (B) has a repeating unit represented by any one of the following formulae (b3-1) to (b3-7). [Chemical formula 2]

[0014] The cyclic olefin polymer resin foamed sheet may be one in which the cyclic olefin polymer (A) is a crystalline olefin polymer.

[0015] It may also be a cyclic olefin polymer resin foam sheet, wherein the relative dielectric constant of the cyclic olefin polymer resin foam sheet measured at a measurement frequency of 2 GHz using a resonant cavity perturbation method is 1.10 to 2.00, and the dielectric loss factor satisfies 0.5×10 -4 ~4.5×10 -4 range.

[0016] In addition, it can also be the following cyclic olefin polymer resin foam sheet, wherein the total reflectivity of the cyclic olefin polymer resin foam sheet is 90% or more relative to the total reflectivity of the alumina reflector in the visible light band of 555nm wavelength as 100%.

[0017] Furthermore, the cyclic olefin polymer resin foam sheet may have an average arithmetic mean surface roughness Ra of 0.50 μm or less in the MD (Machine direction) and TD (Transverse Direction) directions.

[0018] The cyclic olefin polymer resin foam sheet may also be used as a housing for electrical parts, a housing for electronic parts, an electrical insulating material, a sealing material, a protective material, or a high-frequency substrate or a substrate for an electromagnetic wave control component.

[0019] The cyclic olefin polymer resin foamed sheet may be used as a light reflecting plate for a lighting device.

[0020] The cyclic olefin polymer resin foamed sheet may be used for housings for electric parts, housings for electronic parts, electric insulating materials, sealing materials, protective materials, high-frequency substrates, or substrates for electromagnetic wave control components. The cyclic olefin polymer resin foamed sheet may be used for a light reflecting plate of a lighting device. [Effects of the invention]

[0021] According to the present invention, a cyclic olefin polymer resin foam sheet and a method for manufacturing the same can be provided, wherein the cyclic olefin polymer resin foam sheet maintains the stability of mechanical or thermal properties and achieves excellent light reflection characteristics and dielectric properties (low relative dielectric constant, low dielectric loss factor) and surface quality. DETAILED DESCRIPTION

[0022] Cyclic olefin polymer (COP) or cyclic olefin copolymer (COC) has the same glass transition temperature and transparency as polycarbonate, but has very low water absorption like polyolefin and also has very excellent dielectric properties, so it is a particularly useful material as a material for optical systems and electrical and electronic systems. The present invention relates to a resin foam sheet using a cyclic olefin polymer or a cyclic olefin copolymer.

[0023] The cyclic olefin polymer resin foamed sheet of the present invention is composed of a monomer of a cyclic olefin homopolymer (A) or a cyclic olefin copolymer (B), or a mixture of a cyclic olefin homopolymer (A) and a cyclic olefin copolymer (B).

[0024] (Cyclic olefin polymer) The so-called cyclic olefin homopolymer (COP) or cyclic olefin copolymer (COC) refers to a homopolymer or copolymer having an alicyclic structure in the chain, which is synthesized using cyclic olefin as a raw material. In this specification, homopolymers and copolymers are sometimes referred to as polymers. For example, the so-called cyclic olefin polymer may also mean a cyclic olefin homopolymer and a cyclic olefin copolymer. Preferably, the cyclic olefin polymer that can be used in the present invention is a polymer (homopolymer or copolymer) obtained using norbornenes and cyclodienes as raw materials. As a representative example, a homopolymer or copolymer obtained according to the following formula (I) to (VI) can be cited. Furthermore, when referring to a cyclic olefin polymer resin, it is not limited to cyclic olefin polymers, but is intended to include a mixture in which a cyclic olefin polymer is mixed with other polymers, or a composition formulated with additives, etc.

[0025] [Chemical formula 3] [Chemical formula 4]

[0026] According to the formula (I), an addition copolymer of norbornene represented by formula (a1) can be obtained. According to formula (II), a hydrogenated ring-opening metathesis polymer of norbornene of formula (a1) can be obtained. According to formula (III), a trans-cyclic polymer of alkylene norbornene of formula (c1) can be obtained. According to formula (IV), a norbornene addition polymer (d1) represented by formula (a1) can be obtained. According to formula (V), a hydrogenated polymer of a cyclopentadiene polymer represented by formula (e1) can be obtained. According to formula (VI), a hydrogenated polymer of a cyclohexadiene polymer represented by formula (f1) can be obtained. Furthermore, in this specification, a polymer having norbornene of formulas (I) to (IV) as a matrix is ​​sometimes referred to as a norbornene-based resin.

[0027] In the formula, R 1 and R 2 are each independently a hydrogen atom, an alkyl group having 1 to 10 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an alkynyl group having 2 to 10 carbon atoms, an aryl group having 6 to 18 carbon atoms, a hydroxyl group, a halogen atom, or a carboxyl group, and R 1 and R 2 They may be bonded to each other to form a ring. 1 and R 2 The compound forming a ring may be dicyclopentadiene. 1 With R 2 Examples of the ring formed by bonding include a cyclopentane ring, and a norbornane ring which may have an alkyl group having 1 to 3 carbon atoms or a carboxyl group.

[0028] In the formula, R 3It is a hydrogen atom, an alkyl group having 1 to 10 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an alkynyl group having 2 to 10 carbon atoms, an aryl group having 6 to 18 carbon atoms, a hydroxyl group, a halogen atom, a carboxyl group, an acyl group having 2 to 10 carbon atoms, or an alkoxycarbonyl group (the number of carbon atoms is preferably 2 to 12, more preferably 2 to 6, and even more preferably 2 or 3).

[0029] R 1 ~R 3 The position may have any substituent.

[0030] The polymer used in the present invention includes, for example, the cyclic olefin copolymer represented by the formula (a3), the cyclic olefin homopolymer represented by the formula (b3), the cyclic olefin homopolymer represented by the formula (c2), the cyclic olefin homopolymer represented by the formula (d1), the cyclic olefin copolymer represented by the formula (e3), and the cyclic olefin copolymer represented by the formula (f3). Among them, the cyclic olefin copolymer represented by the formula (a3), the cyclic olefin homopolymer represented by the formula (b3), and the cyclic olefin homopolymer represented by the formula (d1) are preferred, and the cyclic olefin homopolymer represented by the formula (b3) is more preferred.

[0031] The norbornene-based hydrogenated ring-opening metathesis polymer of formula (b3) is preferably a polymer containing structural units represented by the following (b3-1) to (b3-7).

[0032] [Chemical formula 5]

[0033] The crystallinity and Tg (Tm) of each compound are as follows.

[0034] In addition, examples of the COP polymer and COC polymer mentioned above can be found in the following documents. ・Harachi Yosuke et al. "Development Trends of Cycloolefin Polymers (Zeiong, Japan)" Polymer Science Society, Vol. 75, No. 6, PP477-485 (Nov., 2018) https: / / www.jstage.jst.go.jp / article / koron / 75 / 6 / 75_2018-0025 / _pdf ·Ohara Masaji "Development and Application of Cycloolefin Polymers" Polymers Vol. 57 August (2008) https: / / www.jstage.jst.go.jp / article / kobunshi1952 / 57 / 8 / 57_8_613 / _pdf ·Ohara Masaji "Development and practical application of cycloolefin polymers" Polyimide-aromatic polymers latest progress 2008 http: / / fibertech.or.jp / JPIC / pdf / 2008_04.pdf

[0035] As a specific product of cyclic olefin homopolymer, a polymer obtained by ring-opening polymerization of norbornene can be cited. As a trade name, ring-opening polymer hydrogenated products of norbornene monomers such as ZEONEX (ZEONEX: registered trademark, manufactured by Zeon Corporation of Japan), ZEONOR (ZEONOR: registered trademark, manufactured by Zeon Corporation of Japan), ARTON (registered trademark, manufactured by JSR Corporation) can be cited (Formula b3-1 to b3-7). As a cyclic olefin copolymer, addition polymers of norbornene monomers such as APEL (registered trademark, manufactured by Mitsui Chemicals Co., Ltd.) and TOPAS (registered trademark, manufactured by Polyplastics Co., Ltd. of Japan) and ethylene can be cited (Formula a-3).

[0036] The resin foam sheet of the present invention comprises any one of a cyclic olefin homopolymer (A) or a cyclic olefin copolymer (B), or a mixture of a cyclic olefin homopolymer (A) and a cyclic olefin copolymer (B). In the case of a mixture, the cyclic olefin copolymer (B) is preferably an elastomer (exhibiting rubber elasticity at room temperature). In the case where the cyclic olefin polymer resin foam sheet comprises a mixture of a cyclic olefin homopolymer (A) and a cyclic olefin copolymer (B), the amount of the cyclic olefin copolymer is preferably added in an amount of 1 to 20 parts by mass relative to 100 parts by mass of the cyclic olefin homopolymer (A). In addition, the cyclic olefin polymer resin foam sheet can also be a resin foam sheet consisting only of a cyclic olefin copolymer (B).

[0037] The cyclic olefin polymer resin foam sheet used in the present invention can also be used as a resin foam sheet formed by a resin composition combined with a functional additive. For example, a flame retardant, a viscosity modifier, an antibacterial / mildewproof agent, a hydrophilic / lipophilic modifier, a morphology stabilizer, an antistatic agent, a colorant, etc. can be added. Although the amount of the additive is not particularly limited, when the additive is added, it can be added within the range of the bubble structure, dielectric properties, surface quality, light reflectivity (total reflectivity) and other properties of the cyclic olefin polymer resin foam sheet.

[0038] Or, by mixing the cyclic olefin polymer to which the present invention relates with other resins, giving mechanical properties such as intensity, impact value, formability, functionality such as heat resistance, can also be used as the cyclic olefin resin foam sheet using resin mixture or resin alloy. The mixed resin is not restricted, as long as it is suitably selected and adopted according to demand. The cyclic olefin polymer to which the present invention relates and the mixing ratio of functional resin are not particularly limited, the same as the situation of additive, can be added in the scope of characteristics such as bubble structure, dielectric properties, surface quality, light reflectivity (total reflectivity) of the resin foam sheet without damaging the mixed cyclic olefin polymer.

[0039] (Average bubble diameter) In the resin foam sheet of the cyclic olefin polymer of the present invention, the average bubble diameter of the bubbles present in the resin constituting the resin foam sheet of the cyclic olefin polymer is specified to be 1 to 20 μm. In the resin foam sheet of the present invention, as described above, the average diameter of the bubbles is small, the relative dielectric constant and the dielectric loss factor can be maintained low, and there is an advantage of being able to obtain excellent properties as an insulating material. In addition, the average bubble diameter is preferably 1 to 18 μm, more preferably 1 to 10 μm or less, further, ideally 1 to 8 μm or less, and further, ideally 1 to 6 μm or less.

[0040] (Bubble number density) The cell number density (cells / mm2) in the cyclic olefin polymer resin foam sheet of the present invention 3 ) is 1.0×10 5 ~6.0×10 8 The optimal range of bubble number density is 1.6×10 5 ~4.8×10 8 , more preferably 1.0×10 6 ~4.8×10 8 , further 6.0×10 6 ~4.8×10 8 In addition, there is a certain relationship between the bubble number density and the average bubble diameter, and there is a general tendency that the bubble number density decreases as the average bubble diameter increases. That is, preferably, the bubble diameter is smaller and the bubble number density is higher, and the two satisfy a prescribed relationship.

[0041] (density, expansion ratio) In the cyclic olefin polymer resin foamed sheet of the present invention, the density of the resin composition is preferably 0.85 g / cm 3 Further, the density is more preferably 0.125 g / cm 3 ~0.80g / cm 3 .

[0042] Although the preferred expansion ratio in the cyclic olefin polymer resin foam sheet of the present invention can be inferred based on the above density, it is shown in advance for the sake of clarity that the expansion ratio is preferably more than 1.2 times, more preferably more than 1.3 times. Although there is no particular upper limit, the expansion ratio can be less than 10 times, and can also be less than 8 times.

[0043] (Method for producing foamed sheet (fine foaming method)) The fine foaming method is a batch method, and the steps are as follows: first, in a high-pressure container, a high-pressure inert gas (for example, nitrogen or carbon dioxide) is fully dissolved as a foaming agent in a solid resin sheet at room temperature until the saturated solubility of the gas is reached, and then the gas in the high-pressure container is depressurized or heated, thereby utilizing the thermodynamic instability of the gas contained in the resin to cause phase separation, thereby foaming the resin. As a specific step example, for example, a method that goes through the following three steps. First, in the method for manufacturing a resin foam sheet of the present embodiment, a step of making a non-reactive gas contained in the resin under pressure is adopted (hereinafter referred to as "the first step"). Subsequently, the step of heating the obtained thermoplastic resin in a temperature range above the crystallization peak temperature of the resin measured by a differential scanning calorimeter and below the melting point peak temperature to foam the resin (hereinafter referred to as "the second step"). Finally, a step of cooling the obtained thermoplastic resin is adopted (hereinafter referred to as "the third step"). The average cell diameter of the foamed sheet can be adjusted by the holding time and the holding temperature in the second step.

[0044] (Total light reflectance regulation) The total light reflectance of the cyclic olefin polymer resin foam sheet of the present invention is preferably 90% or more relative to the reflectance of the alumina reflector in the visible light band of 555nm wavelength as 100%. The total reflectance is more preferably 94% or more, and more preferably 98% or more. The cyclic olefin polymer resin foam sheet of the present invention can be used by laminating the cyclic olefin polymer as a transparent resin on other resins according to the application.

[0045] (Relative dielectric constant, dielectric loss factor) Since the foam sheet has a low relative dielectric constant and a low dielectric loss factor, it can exert suitable performance when used for housings for electrical parts, housings for electronic parts, electrical insulating materials, sealing materials, protective materials, or substrates for high-frequency electromagnetic wave control components. Based on this viewpoint, the relative dielectric constant of the foam sheet is preferably 1.10 to 2.00, more preferably 1.10 to 1.50, and most preferably 1.10 to 1.35. The dielectric loss factor (tan δ) is preferably 0.5×10 -4 ~4.5×10-4 , more preferably 1.0×10 -4 ~3.5×10 -4 , and the most preferred value is 1.0×10 -4 ~2.5×10 -4 , and more preferably 1.0×10 -4 ~2.0×10 -4 the following.

[0046] (Arithmetic mean surface roughness) When an alternating current flows through a conductor, there is a skin effect, that is, the higher the frequency of the current, the less likely it is to flow to the center of the conductor, and it only flows to the surface. In addition, the relationship between the surface roughness and transmission loss of high-frequency copper circuits is that if the surface roughness is greater than the epidermis depth, the signal transmission path becomes longer and the signal loss becomes more. On the contrary, if the roughness is less than the epidermis depth, the transmission is smaller, the transmission path becomes shorter, and the signal loss becomes less. Therefore, the lower the surface roughness of the foam sheet, the better. In particular, in high-frequency bands such as GHz bands or THz bands, the surface properties of the foam sheet will affect the surface properties of the circuit material and there is a possibility of affecting the loss. In addition, in resin foam sheets that are expected to be used in circuit substrate materials, etc., if the further high-precision of the circuit is considered in the future, and considering the influence of the roughness of the substrate surface on the surface properties of the stacked circuit, it is necessary to reduce the surface roughness of the foam sheet. Here, as the surface roughness, since the uniform roughness of the sheet surface is important, the surface roughness in the present invention uses the arithmetic average surface roughness Ra. Based on this viewpoint, the arithmetic average surface roughness Ra of the cyclic olefin polymer resin foamed sheet is 0.08 to 0.50 μm, preferably 0.10 to 0.50 μm, more preferably 0.10 to 0.35 μm, further preferably 0.10 to 0.30 μm, and most preferably 0.10 to 0.25 μm.

[0047] The thickness of the cyclic olefin polymer resin foam sheet of the present invention is at most 2 to 3 mm. Specifically, although it can be determined according to the purpose, if it is considered to be applied to the housing or reflector of electronic parts, it can be set to, for example, a range of 50 μm to 2 mm, preferably a range of 100 μm to 1 mm, and more preferably a range of 0.5 mm to 1 mm. Since the cyclic olefin polymer resin foam sheet of the present invention is manufactured by impregnating the foaming gas into the cyclic olefin polymer resin foam sheet recorded separately and foaming the gas under specified conditions, a resin foam sheet with excellent surface quality as described above can be obtained. In addition, after the fine foaming method is completed, rolling can be performed as needed in order to adjust the plate thickness and surface properties. Therefore, the reason why the surface roughness of the resin foam sheet of the present invention as a surface quality is excellent is that because the gas permeation step and the foaming step are separated in the foaming method, the bubble diameter can be made smaller and the bubble diameter distribution can be made more stable. Therefore, the surface properties are likely to be stabilized, and by combining the roll processing as described above, the arithmetic mean surface roughness Ra, which is an index of surface roughness, can be suppressed to a low level.

[0048] (Purpose of use) The cyclic olefin polymer resin foam sheet of the present invention can be used for high-quality housings for electrical parts, housings for electronic parts, electrical insulating materials, sealing materials, protective materials, substrates for high-frequency electromagnetic wave control components, or light reflecting plates for lighting devices by utilizing its low relative dielectric constant and low dielectric loss factor. In this case, the surface properties or light reflectivity are excellent, so it is advantageous when using the above materials.

[0049] The demand for low dielectric materials is getting higher and higher. For example, in the field of mobile phone services, the introduction of the fifth generation (5G) mobile communication system began overseas in 2019, and Japan started 5G mobile communication systems in 2020, etc., which also opened a new system with high speed, large capacity, low latency, and simultaneous connection of multiple devices. Cars are developing advanced driver assistance systems (ADAS, Advanced Driver Assistance System) and selling L3 level (Level 3) self-driving cars, etc., and the practical application of new technologies is being carried out in automobiles. Supporting such technology are printed wiring boards and antenna substrates corresponding to high frequencies such as Sub-6 bands and millimeter bands. Since the transmission loss of radio waves increases with the increase in frequency, the role of the low dielectric substrate that suppresses the loss becomes larger. In addition, as described at the beginning of this article, it is required to deal with the megahertz band, and the cyclic olefin polymer resin foam sheet of the present invention can also be used well for this.

[0050] The cyclic olefin polymer resin foam sheet of the present invention has an extremely high total light reflectance. As its use, as mentioned above, a light reflecting plate of a lighting device can be cited. With the improvement of power saving awareness, LED (Light Emitting Diode) is being developed for general lighting in residences, offices, shops, etc. In the interior of the car, the lighting brought about by miniaturization, the improvement of luminous efficiency, the low cost of LED light sources, indoor lights or lighting lamps, the freedom of design and other advantages are used to show the interior space and improve the product value. The cyclic olefin polymer resin foam sheet according to the present invention can meet the above-mentioned needs through its extremely high total light reflectance. In addition, since it is also excellent in formability, it can be processed into a shape corresponding to the lighting form or the setting of the site restrictions to provide a reflecting plate. [Example]

[0051] (Materials used) Cyclic olefin polymers (1) ZEONEX C2420 manufactured by Zeon Corporation of Japan (Based on the melting point, it is estimated to be a syndiotactic resin of DCP) (2) ZEONEX 790R (norbornene-based resin) manufactured by Zeon Co., Ltd. (3) ZEONOR 1420R (norbornene-based resin) manufactured by Zeon Co., Ltd. (4) ZEONEX K22R (norbornene-based resin) manufactured by Zeon Corporation of Japan Glass transition temperature (JISK7121): 143°C (5) ZEONEX T62R (norbornene-based resin) manufactured by Zeon Corporation of Japan Glass transition temperature (JISK7121): 154°C (6) Cyclic olefin copolymer (COC) elastomer: TOPAS E-140 manufactured by Polyplastics Co., Ltd. A non-crystalline resin (norbornene-based resin) produced by TOPAS Advanced Polymers GmbH. The tensile modulus is 50MPa and the tensile elongation at break exceeds 500% (ISO 527-T2 / 1A), an elastomer that maintains excellent ductility even in low temperature ranges below freezing. (7) Cyclic olefin copolymer (COC): TOPAS 5013L-10 (norbornene-based resin) manufactured by Polyplastics Co., Ltd. (8) Cyclic olefin copolymer (COC): TOPAS 6015 (norbornene-based resin) manufactured by Polyplastics Co., Ltd.

[0052] <Production of Example Materials as Samples> A rolled body of the cyclic olefin polymer sheet is obtained, and the rolled body is placed in a pressure vessel, and the pressure vessel is pressurized to 5.2 MPa by carbon dioxide, and the carbon dioxide is allowed to permeate the resin film for 24 hours. After the steps, the rolled body is taken out from the pressure vessel, and the cyclic olefin polymer sheet is foamed (by continuously supplying it to a hot air circulation foaming furnace set at 140°C to 260°C and maintaining it for a prescribed time to foam it), and a cyclic olefin polymer resin foamed sheet is obtained. In addition, a non-foamed resin sheet that is not permeated with carbon dioxide is used in the comparative material. Here, regarding the holding temperature during foaming of each test material, Example material 1 to Example material 4 are maintained at 260°C, Example material 5 to Example material 8 are maintained at 170°C, and Example materials 9 and 10 are maintained at 140°C to foam them.

[0053] (Measurement method) The expansion ratio and the foam density were measured as follows. <Measurement method of foaming ratio> The expansion ratio is the apparent ratio commonly used for resin foams. A 10 cm x 10 cm test piece is cut from the resin foam sheet and weighed (W1 [g]). The thickness at the four corners and the center of the test piece is then measured (the measuring machine is based on JIS K6767 method). The average value (T [cm]) of the five points is used to calculate the apparent ratio according to the following formula (1). Apparent ratio (foaming ratio) = 10 × 10 × T / W1…(1)

[0054] <Measurement method of foam density> The density of the resin foam sheet is measured in accordance with JIS K7222-1999 "Foamed plastics and rubbers - Determination of apparent density". A 10 cm x 10 cm specimen is cut out from the resin foam sheet conditioned at 23°C ± 2°C for 72 hours or more after molding. Specifically, the foam density is calculated according to the following formula (2). The unit is g / cm 3 . [Mathematical formula 1] ρ a ={(m+ma)} / V … (2) m is the mass of the specimen (g), V is the volume of the specimen (cm 3), ma is the mass of the displaced air (g). Since the expansion ratio is low, ma (mass of replaced air) is negligible, so ma is ignored for calculation. Five measurements were performed, and the average value was calculated from the measurement results of all the test pieces and used as the density.

[0055] <Measurement method of bubble diameter> The bubble diameter is calculated according to ASTM D3576-77. Take a SEM (Scanning Electron Microscope) photograph of the longitudinal section of the sheet, draw straight lines in the horizontal and vertical directions on the SEM photograph, and average the bubble chord lengths t that are crossed by the straight lines. The magnification of the photograph is taken as M, and introduced into the following formula to calculate the average bubble diameter d (d = t / (0.616 × M)). Regarding the average bubble diameter, SEM photographs are measured at three different fields of view in the center of the width direction, and the average value is taken as the average bubble diameter.

[0056] <Measurement method of bubble number density> A SEM photograph of the longitudinal section of the cyclic olefin polymer resin foamed sheet was taken. Five 100 μm×100 μm areas were randomly selected on the SEM photograph, and the number of bubbles in each area was counted. From each count value, the number of bubbles per 1 mm in each area was calculated. 2 The number of bubbles is calculated based on the area per 1 mm 3 Calculate the number of bubbles per 1mm in each of the five areas. 2 The average value of the number of bubbles is taken as the bubble density (cells / mm 2 ). By dividing the obtained 2 The number of bubbles is multiplied by (3 / 2) and used as the value per 1mm in each area. 3 The number of bubbles is calculated based on the 5 areas per 1mm 3 The average value of the number of bubbles is taken as the bubble density (cells / mm 3 ). When measuring the cell diameter or the cell number density, it is ideal to prepare a plurality of (preferably 3 or more) SEM photographs and average the values ​​calculated in the respective SEM photographs.

[0057] <Calculation method of total light reflectance> The total reflectance of light was measured as follows. A spectrophotometer U-4100 (trade name) manufactured by Hitachi High-Tech Fielding was used to measure the total reflectance of the sample at a wavelength of 550 nm. A reference was used as an alumina white plate (210-0740 (trade name), manufactured by Hitachi High-Tech Fielding (stock)), and the relative value relative to the reference was used as the measured value.

[0058] <Measurement of relative dielectric constant and dielectric loss factor> The relative dielectric constant and dielectric loss factor were measured using the cavity perturbation method with the measurement frequency set to 2 GHz. r The dielectric loss factor tanδ and the multiple dielectric constants of the cyclic olefin polymer resin foam sheet in the plane direction can be measured by the resonant cavity method. In the present invention, the relative dielectric constant system is measured by the resonant cavity method at a resonant frequency of 2 GHz using a sample of 78 mm in length × 2.4 mm in width × 1 mm in thickness. As the device used for measurement at this time, for example, the resonant cavity can use CP461 manufactured by Kanto Electronics Application Development Co., Ltd., and the network analyzer can use E8361A manufactured by Agilent Technologies.

[0059] <Measurement of surface roughness> Regarding the evaluation of the surface properties, in order to evaluate the overall surface properties of the foamed sheet, the surface properties of the foamed sheet of the present invention were evaluated by measuring Ra instead of Rz which is greatly affected by the maximum roughness and the like. According to JIS B0601: 2013, the arithmetic mean roughness of Ra is determined. HANDYSURF E-30A (manufactured by Tokyo Seimitsu Co., Ltd.) was used in the measurement. In each measurement, the standard length was set to 2.5 mm. In the present invention, when the surface roughness Ra is, for example, less than 1.0 μm, it means that on the surface of the foam sheet, 5 measurement lines are randomly determined in the MD direction, and the arithmetic mean roughness of the measurement values ​​in each measurement line is measured to obtain the average roughness of 5 measurement values, and 5 measurement lines are randomly determined in the TD direction. The average value of the average roughness in the two directions is less than 1.0 μm. That is, the surface roughness in the present invention is evaluated by the average value of the two directions of the MD direction and the TD direction. Here, since the surface roughness is applied not only in the MD direction but also in the TD direction as a surface characteristic, the reason for taking the average value of the two directions is that when the sheet is manufactured, it is sometimes passed through a roller. At this time, the sheet is stretched by the surface pressing effect generated by the roller in the MD direction, and therefore the surface properties in the MD direction are often better than those in the TD direction.

[0060] <Materials used for the test> The materials used for the test were 12 types of COP-based resins in total, namely, the following Example materials 1 to 10 and Comparative Example materials 1 and 2. Comparative Example materials 1 and 2 were non-foamed sheets having the same composition as that of the Example materials.

[0061] Example material 1 is a foamed sheet using ZEONEX C2420 monomer as a COP resin, and Example materials 2 to Example materials 4 are foamed sheets using ZEONEX C2420 as a COP resin as a main component, and adding a predetermined amount of TOPAS E140 as a COC elastomer in a gradually increasing amount. Here, Example material 2 is a foamed sheet in which 5% by mass of COC elastomer TOPAS E140 is added to 95% by mass of ZEONEX C2420, Example material 3 is a foamed sheet in which 10% by mass of COC elastomer TOPAS E140 is added to 90% by mass of ZEONEX C2420, and Example material 4 is a foamed sheet in which 20% by mass of COC elastomer TOPAS E140 is added to 80% by mass of ZEONEX C2420. In addition, Example Materials 5 to 8 are foams in which the types of COP resins are changed in various ways. Specifically, Example Material 5 is a foam using ZEONOR 790R as the COP resin, and Example Material 6 is a foam using ZEONOR 1430R as the COP resin. Example Material 7 is a foam sheet using ZEONEX K22R, and Example Material 8 is a foam sheet using ZEONEX T62R. Example material 9 is a COC resin foam sheet using TOPAS 5013L-10 as the COC resin, and Example material 10 is a COC resin foam sheet using TOPAS 6015 monomer as the COC resin. Comparative Example 1 shows the relative dielectric constant and dielectric loss factor of ZEONEX C2420 as a non-foamed COP resin, and Comparative Example 2 is a non-foamed sheet composed of 80 mass % of COP resin and 20 mass % of COC elastomer mixed together. The composition of comparative material 1 is the same as that of example material 1, and the composition of comparative material 2 is the same as that of example material 4.

[0062] <Test results of physical properties evaluation of test materials foam sheets> Table 1 shows the results of evaluating the physical properties of Example Materials 1 to 10 and Comparative Example Materials 1 and 2 used in the tests.

[0063] <Foaming ratio and density of COP-based resin foam sheets> The foamability of the example materials was evaluated based on the foaming ratio and density. The foaming ratios of Example Materials 1 to Example Materials 10 were in the range of 1.4 to 6.7 times, which were low foaming ratios of less than 10 times. In particular, excluding Example Materials 4 and Example Materials 2, which obtained a maximum bubble diameter of 16.0 μm, the foaming ratios of the other example materials did not reach 6 times. In contrast, Example Materials 9 and Example Materials 10, which were foam sheets using only COC resin, had low foaming ratios of less than 2 times. In contrast, the foam densities of Example Materials 1 to 10 were 0.15 to 0.72 g / cm 3 The foaming ratio is within the range of 10 times or less, so there is no foam with a foam density of less than 0.1. The foam sheet of Example Material 4 with a maximum bubble diameter of 16.0 μm has the lowest density, which is 0.15 g / cm 3 In addition, the foaming ratios of Example Material 9 and Example Material 10 are both relatively low, 1.4 times and 1.6 times, respectively, so the foam density is 0.72 and 0.64 g / cm 3 high value.

[0064] <Characteristics related to the cell structure of COP-based resin foam sheets> When the Example materials 1 to 10 were foamed, none of the test materials had any foaming hindrance, and foaming could be performed without any particular problems, thereby obtaining a predetermined foamed sheet. The bubble structure in the present invention can be appropriately adjusted by changing the composition of the material constituting the foam and the foaming conditions. Here, if the average bubble diameter, average bubble number density, and foam density of the foamed sheet in the present invention are observed, the average bubble diameter of the Example materials as a whole can be 1.2 μm to 16.0 μm, and the bubble number density of 1.6×10 5 ~4.8×10 8 pcs / m 3 , the foam density is in the range of 0.15 to 0.72. In Example Materials 1 to Example Materials 4, if the results of the foamed sheet in which ZEONEX C2420 as a COP resin is used as the main component and gradually increased on one side, and a specified amount of TOPAS E140 as a COC elastomer is added, it can be seen that by increasing the COC elastomer, the bubbles grow through foaming, and the average bubble diameter can be increased. As a result, it is believed that the bubble number density and the foam density can be reduced. On the other hand, when using only COP resins other than ZEONEX C2420 and not containing COC elastomer, Example Materials 5 to 8, the average cell diameter is smaller and the cell number density is higher than Example Materials 2 to 4 in which a predetermined amount of COC elastomer is added to the COP resin. This is considered to be because, in the case of a resin in which a COC elastomer is added to the COP resin, the addition of the COC elastomer produces an improvement effect on viscoelastic properties, such as an increase in melt tension near the foaming temperature. In addition, although there are foamed sheets using only COC resin, such as Example Materials 9 and 10, in these cases, it is clear that foaming characteristics such as cell structure differ depending on the type of COC resin. In addition, it goes without saying that the cell structure in the present invention, in addition to the cell structure disclosed in the embodiments, can obtain a cell structure different from but similar to that disclosed in the embodiments by appropriately changing the composition of the material constituting the foam and the foaming conditions.

[0065] <Measurement results of total reflectance of COP-based resin foam sheet> In Example Materials 1 to 10, the ratio of the total reflectance to the alumina standard plate in the visible light band of 550 nm wavelength was 90% or more, and the average bubble diameter was 20 μm or less. Specifically, by introducing bubbles of 1.2 to 16.0 μm or less, a resin foam sheet with high light reflectance was obtained. In addition, although the data of diffuse reflectance was not specifically measured, in the case of the resin foam sheet of the present invention, since fine bubbles were introduced, it can be inferred that its diffuse reflectance is also high. In Example Materials 1 to 8, the total reflectance ratio of the COP resin monomer or the resin foam sheet in which 5% to 20% by mass of COC resin is mixed with the COP resin monomer to the alumina standard plate is 98.5 to 99.8%, while the total reflectance of Example Materials 9 and 10, in which the COC resin composition is 100%, is 94.4% and 98.6%, respectively, which clearly shows a tendency to be slightly inferior to Example Materials 1 to 8. It is believed that this difference is caused by the difference in the resin composition of the foam.

[0066] <Measurement results of relative dielectric constant and dielectric loss factor of COP-based resin foam sheet> The relative dielectric constants of Example Materials 1 to 10 were in the range of 1.11 to 1.77, and the dielectric loss factors were 1.0×10 -4 ~2.2×10 -4 In addition, in Example Materials 1 to 4, when the dielectric properties of the foamed sheets were measured by adding a predetermined amount of TOPAS E140 as a COC elastomer in a stepwise manner within the range of 0 to 20 parts by mass while using ZEONEX C2420 as a COP resin as the main component, the relative dielectric constant was 1.11 to 1.32, and the dielectric loss factor was 1.0×10 -4 ~2.0×10 -4 range. It is believed that the relative dielectric constant or dielectric loss factor of the material containing a specified amount of COC elastomer is lower, and the material containing a larger average cell diameter and a specified cell number density by adding COC elastomer is slightly superior in dielectric properties. In contrast, Example Materials 5 to Example Materials 8 in which the type of COP resin was changed had a relative dielectric constant of 1.21 to 1.32 and a dielectric loss factor of 1.2×10 -4 ~1.4×10 -4 , which are almost the same. In contrast, the relative dielectric constant and dielectric loss factor of Example Materials 9 and 10, in which the COC resin composition is 100%, are greater than those of Example Materials 1 to 8. The relative dielectric constant of Example Material 9 is 1.77, and the dielectric loss factor is 2.2×10 -4 , the relative dielectric constant of Example material 10 is 1.68, and the dielectric loss factor is 2.1×10 -4 . Here, it is presumed that the dielectric properties of Example Materials 9 and 10 are inferior to those of other Example Materials because the structures of COP resin and COC resin are different. In addition, the relative dielectric constants of the non-foamed sheets with the same composition as Example Materials 1 and 4 are 2.34 and 2.13, respectively, and the dielectric loss factor is 5.0×10 -4 , 2.8×10 -4 , the relative dielectric constant is above 2.00, and the dielectric loss factor is also over 2.5×10 -4 .

[0067] <Measurement results of arithmetic mean surface roughness Ra of COP-based resin foam sheet> The arithmetic mean surface roughness Ra of Example Materials 1 to 10 is in the range of 0.10 to 0.50 μm. Here, in a little more detail, if the difference between the materials is observed, regarding the foamed sheets of Example Materials 1 to 4, which change the foaming ratio and the bubble diameter by changing the content of the COC elastomer TOPAS E-140 in the ZEONEX C2420 of COP, although the average bubble diameter of Example Material 4 is 16.0 μm (greater than 10 μm) and the surface roughness is also relatively large, 0.50 μm, the difference between the materials of Example Materials 1 to 3, whose average bubble diameters are 2.7 to 3.8 μm, has been confirmed, but the difference is not that large. It is believed that the reason is that in the case of Example Material 4, the average bubble diameter is relatively large, 16.0 μm, so the change of the bubble structure inside the foam body caused by the growth of bubbles during the foaming method has an effect on the surface roughness of the foamed sheet surface. In contrast, in the case of Example Materials 5 to 8, which use a different type of COP resin from Japan Zeon, or Example Materials 9 to 10, which use COC resin from Polyplastics Co., Ltd., although the difference between the materials is recognized, the surface roughness of the former is in the range of 0.15 μm to 0.23 μm, while the surface roughness of the latter is in the range of 0.12 to 0.13 μm. Even if the entirety of Example Materials 5 to 10 is evaluated, the surface roughness is also in the range of 0.12 to 0.23 μm. If Example Material 4 is excluded, the surface roughness of Example Materials 1 to 10 satisfies 0.30 μm or less, and further satisfies 0.25 μm or less, and the difference in surface roughness between the materials is not that great. It is believed that the reason for this is that since the average bubble diameter of these foam sheets is small, being 5 μm or less, the effect of bubble growth on the surface roughness of the foam surface is small, and the effect of increasing the surface roughness of the foam surface by bubble growth overlaps with the effect of improving the surface roughness caused by the stretching effect of the resin in a softened state during foaming. In addition, in the case of the unfoamed sheets of Comparative Example Materials 1 and 2, the surface roughness exceeded 0.20 μm.

[0068] <Summary of test results> According to the results of the examples, the foamed sheets using the cyclic olefin polymers (Example Material 1 to Example Material 10) that meet the requirements of the present invention all have excellent light reflection properties and dielectric properties (low relative dielectric constant, low dielectric loss factor) and good surface quality. In particular, the COC monomers of Example Materials 2 to Example Materials 4, in which a mixture of a cyclic olefin copolymer (COC) and COC is added in a range of 20% by mass to a cyclic olefin polymer (COP) as a cyclic olefin polymer, or Example Materials 5 to Example Materials 8, and Example Materials 9 and Example Materials 10 in which the type of cyclic olefin polymer is changed, can achieve the above-mentioned effect, and can obtain results showing more excellent light reflection characteristics and dielectric properties (low relative dielectric constant, low dielectric loss factor) and surface quality. In contrast, the cyclic olefin polymer of the comparative material is not foamed, and its relative dielectric constant shows a value that is at least about 0.4 higher than that of the example material. The dielectric loss factor of the comparative material is also relatively high, which is 1.0×10 -4 ~2.2×10 -4 , while in Comparative Example 1 it is 5.0×10 -4 , showing extremely high values.

Claims

1. A cyclic olefin polymer resin foam sheet, characterized in that: It is composed of either monomers of the cyclic olefin homopolymer (A) or the cyclic olefin copolymer (B), or a mixture of the cyclic olefin homopolymer (A) and the cyclic olefin copolymer (B), and has an average cell diameter of 1 to 20 μm.

2. The cyclic olefin polymer resin foamed sheet according to claim 1, wherein The cyclic olefin copolymer (B) is a cyclic olefin elastomer, and the cyclic olefin elastomer is added in an amount of 1 to 20 parts by mass based on 100 parts by mass of the cyclic olefin homopolymer (A).

3. The cyclic olefin polymer resin foamed sheet according to claim 1, wherein The cyclic olefin homopolymer (A) or the cyclic olefin copolymer (B) has a repeating unit represented by any one of the following formulae (a3), (b3), (c2), (d1), (e3), and (f3), [Chemical formula 1] In the formula, R 1 and R 2 are each independently a hydrogen atom, an alkyl group having 1 to 10 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an alkynyl group having 2 to 10 carbon atoms, an aryl group having 6 to 18 carbon atoms, a hydroxyl group, a halogen atom, or a carboxyl group, and R 1 and R 2 They can also be bonded to each other to form a ring; wherein R 3 It is a hydrogen atom, an alkyl group having 1 to 10 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an alkynyl group having 2 to 10 carbon atoms, an aryl group having 6 to 18 carbon atoms, a hydroxyl group, a halogen atom, a carboxyl group, an acyl group having 2 to 12 carbon atoms, or an alkoxycarbonyl group having 2 to 12 carbon atoms.

4. The cyclic olefin resin foamed sheet according to claim 3, wherein The cyclic olefin homopolymer (A) or the cyclic olefin copolymer (B) has a repeating unit represented by any one of the following formulae (b3-1) to (b3-7); [Chemical formula 2] 5. The cyclic olefin polymer resin foamed sheet according to any one of claims 1 to 4, wherein The cyclic olefin polymer (A) is a crystalline olefin polymer.

6. The cyclic olefin polymer resin foamed sheet according to any one of claims 1 to 4, wherein The relative dielectric constant of the cyclic olefin polymer resin foamed sheet measured at a measurement frequency of 2 GHz using a resonant cavity perturbation method is 1.10 to 2.00, and the dielectric loss factor satisfies 0.5×10 -4 ~4.5×10 -4 range.

7. The cyclic olefin polymer resin foamed sheet according to any one of claims 1 to 4, wherein The total reflectance of the cyclic olefin polymer resin foamed sheet is 90% or more relative to the reflectance of an alumina reflector in the visible light band of 550 nm wavelength, assuming the reflectance of the alumina reflector to be 100%.

8. The cyclic olefin polymer resin foamed sheet according to any one of claims 1 to 4, wherein The average arithmetic mean surface roughness Ra of the cyclic olefin polymer resin foamed sheet in the MD direction and the TD direction satisfies 0.50 μm or less.

9. The cyclic olefin polymer resin foamed sheet according to claim 6, wherein The cyclic olefin polymer resin foamed sheet is used for housings for electric parts, housings for electronic parts, electric insulating materials, sealing materials, protective materials, high-frequency substrates, or substrates for electromagnetic wave control components.

10. The cyclic olefin polymer resin foamed sheet according to claim 7, wherein The cyclic olefin polymer resin foamed sheet is used as a light reflecting plate of a lighting device.

11. Use of the cyclic olefin polymer resin foam sheet according to claim 6, which is used for housings for electric components, housings for electronic components, electric insulating materials, sealing materials, protective materials, high-frequency substrates, or substrates for electromagnetic wave control components.

12. Use of the cyclic olefin polymer resin foamed sheet according to claim 7 for a light reflecting plate of a lighting device.

Citation Information

Patent Citations

  • Foam and its use

    JP1999100454A

  • polymer foam

    JP1999514680A

  • Resin foam

    JP2013189484A

  • Cyclic olefin-based resin foam particle, manufacturing method therefor, and foam molded body

    JP2017179238A

  • Coaxial cable

    WO2009041116A1

Cited By

  • COC microcellular foam material and preparation method thereof

    CN119931133A